The Influence of Organizational Learning Capability and Organizational Creativity on Organizational Innovation (Study At PT XYZ) - Nabila Dwi Hilmiyanti; Retno Kusumastuti (Hasanuddin Economics and Business Review, 2021)
Technology changes make the organization forced to be flexible and quickly adapt to the fickle innovation and environment. Learning and creativity are the things that can support the realization of innovation. This study aims to determine the influences of organizational learning capability and organizational creativity on organizational innovation at PT XYZ through the individual perception. This research uses quantitative methods with data collection through surveys distributed by questionnaire and uses total sampling with 101 employees. To find out the relationship between variables, this study uses multiple regression analysis techniques. The results of this study indicate that there is a relationship between organizational learning capability and organizational creativity on organizational innovation at PT XYZ.